STUDENTS’ – FUTURE DOCTORS AND PHARMACISTS PROFESSIONAL COMPETENCE FORMATION - Gumenyuk, Olga M. (Educological discourse, 2014)
The article describes the role of the phenomenon of “self-concept” in terms of modern psychology and pedagogy, the formation of professional competence of doctors and pharmacists. Stages of formation and stabilization of professional competence of future doctors (pharmacist) disclosed as a result of the systematization of observation data.